On Korn’s Inequality for Nonconforming Finite Element - Knobloch, P. (Technische Mechanik - European Journal of Engineering Mechanics, 2019)
We investigate the validity of discrete Korn’s inequality for general nonconforming finite element spaces defined over triangulations consisting of triangles and/or quadrilaterals. We show that for spaces satisfying the patch test of order 2 the discrete Korn inequality holds whereas it fails for spaces satisfying the patch test of order 1 only.